Juridical Analysis of Letter C as the basis for rights in obtaining proof of ownership of land rights - Dekafela, Karina Via; Darmadi, Nanang Sri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
The Letter C quote is proof of tax payments in the colonial period which used the fiscal cadaster system, namely a land registration system oriented towards tax collection. However, after the Indonesian nation became independent, what applied was recht cadaster, namely land registration which prioritizes legal ownership of land rights. This research aims to determine the position of Letter C as a basis for rights in legislation and jurisprudence and to determine the factors that influence the use of Letter C as a basis for rights in obtaining proof of ownership of land rights. The type of research used is normative juridical, the Statute Approach method, using secondary data with data collection methods for primary, secondary and tertiary legal materials, using prescriptive data analysis. Based on the research it was found that: (1) There are differences between the statutory provisions, namely the ATR Ministerial Regulation No.3 of 1997 and the Agrarian Ministerial Regulation No. 2 of 1962 which places Letter C as the basis for rights in obtaining proof of ownership of land rights while the Supreme Court Decision dated 10 February 1960 No.34/K/Sip/1960 views Letter C only as proof of tax payments. (2) Factors hindering the use of Letter C as a basis for rights in obtaining proof of ownership of land rights include: (a) Differences in the accuracy of land measurements (b) The community still considers Letter C as proof of land ownership (c) The community considers land registration require high costs.